Biological Activity and Taxonomy of Persea americana Mill: A Systematic Review - Abdulrahman Mahmoud Dogara (Eurasian Journal of Science and Engineering)
Medicinal plants are the main raw materials utilized in the manufacture of pharmaceutical products around the world. Avocado (Persea americana Mill.) is a high-nutrient tropical fruit of the Lauraceae family. The study provides a concise summary of the most important results from the many studies conducted on P. americana since 2010 that have sought to identify active principles found in the plant that can treat human ailments. To find published articles, searches were conducted through Google Scholar, PubMed, ScienceDirect, Web of Science, BioMed Central, Science, Scopus, and Springer. In the 113 articles published, it was discovered that the plant extract worked well against cancer, free radicals, bacteria, parasites, inflammation, and diabetes. The chemical compound that was mentioned the most frequently was polyphenol. Clinical studies involving humans are necessary to confirm and improve the effectiveness of avocado seed, peel, and leaf extracts in the treatment of diseases. Although the safety of avocado extract has been shown in animal models, it is imperative to evaluate the dosage and potential adverse effects in humans before deeming it an effective and safe treatment. The extract of P. americana may have a significant impact on the advancement of nutraceuticals.